The Surgical Care Improvement Project Antibiotic Guidelines: Should We Expect More Than Good Intentions?. (August 2015) - Schonberger, Robert B.; Barash, Paul G.; Lagasse, Robert S.
Abstract : Since 2006, the Surgical Care Improvement Project (SCIP) has promoted 3 perioperative antibiotic recommendations designed to reduce the incidence of surgical site infections. Despite good evidence for the efficacy of these recommendations, the efforts of SCIP have not measurably improved the rates of surgical site infections. We offer 3 arguments as to why SCIP has fallen short of expectations. We then suggest a reorientation of quality improvement efforts to focus less on reporting, and incentivizing adherence to imperfect metrics, and more on creating local and regional quality collaboratives to educate clinicians about how to improve practice. Ultimately, successful quality improvement projects are behavioral interventions that will only succeed to the degree that they motivate individual clinicians, practicing within a particular context, to do the difficult work of identifying failures and iteratively working toward excellence.